Sense and Difference. A reflection on the meaning of human life in the techno-scientific era - Marcos, Alfredo (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Modernity has given us powerful tools, but has plunged us into a certain ignorance of the sense (section 1). To investigate on the sense or meaning I propose recover two ancient maxims: «become who you are» and «know thyself» (section 2). In fact, self-knowledge and self-realization are simultaneous. Therefore, we will need an understanding of our human nature as well as of our personal constitution. We will present a theory of human nature close to common sense and to the Aristotelian tradition, according to which we are rational social animals (section 3). This gives us some guidance for life. However, my life has to be conducted depending on the person I am. Can we get knowledge about this? The answer comes through the notion of difference (section 4). The constitutive difference is unique to each person, and is formal, then, in principle, knowable. But in order to know it, one need to meet many resources, including science and more.